HYBRID WATER-TREATMENT PLANTS APPLICATION AT CIRCULATING COOLING SYSTEMS BLOW-WATER PREPARING - Кишневский, В. А.; Кишневский, Е. В.; Малиновский, О. М.; Шуляк, И. Д. (Water and Water Purification Technologies. Scientific and Technical News, 2011)
Probable hybrid schemes of water-treatment including reverse osmosis system (ROS) for cleaning heat-transmitter in energy are considered in the article. Internally staged design (ISD) principle (construction into the stage) application possibility is considered in the hybrid scheme of water treatment. The comparative analysis of the circulating cooling systems (CCS) blow-water treatment in hybrid schemes with complete utilization of exhaust cation filters regeneration solutions and ROS concentrate is conducted.